(untitled) (Medico Legal Update, 2020)
Hormonal deficiencies may contribute to the development of abnormalities of oral and vaginal tissues, such as pain, desquamation, recurrent oral, vaginal ulceration and delayed post-surgical healing .This study was done to determine the differences of cell activity in oral and vaginal mucosa . A total of 200 females of different age groups were used in this study Oral smears were obtained from the buccal mucosa by scraping the area gently using a wooden tongue depressor while vaginal smears were obtained from the proximal portion of the lateral wall of the vagina using Ayre’s spatula by scraping the area gently . In order to find to change in mucosa during different phases of menstrual cycle . In two groups the present results revealed that vaginal cytological patterns of each group is similar to the oral cytological pattern with some differences . In conclusion significant correlation between the hormonal fluctuations in woman and the degree of maturation of their oral epithelium was revealed in this study .